2014
DOI: 10.1186/s13018-014-0051-1
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal component alignment is less reliable than coronal component alignment in a Chinese population undergoing navigated TKA

Abstract: BackgroundThe purpose of our study was to determine whether postoperative sagittal component alignments of primary total knee arthroplasty (TKA) using the conventional and navigated technique differed significantly. Additionally, we determined whether the use of navigation systems resulted in hyperextension of the femoral components in Chinese patients.MethodsThis retrospective study reviewed 36 consecutive patients (72 knees) who underwent simultaneous bilateral primary TKAs at our hospital from February 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Young-Hoo Kim et al [30] studied 3018 patients who underwent total knee arthroplasty, they thought that when total knee components in the position of:femoral coronal alignment, 2-8°valgus; femoral sagittal alignment, 0-3°; tibial coronal alignment, 90°; tibial sagittal alignment, 0-7°; femoral external rotational alignment, 2-5°; tibial external rotational alignment, 2-5°; and overall anatomical knee alignment at an angle of 3-7.5°valgus, the survival rate of the prosthesis could improve. Whether coronal femoral shaft bowing or sagittal femoral shaft bowing, the femoral component alignments in the coronal plane or sagittal plane were affected [7,23]. The view was further con rmed in our study.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Young-Hoo Kim et al [30] studied 3018 patients who underwent total knee arthroplasty, they thought that when total knee components in the position of:femoral coronal alignment, 2-8°valgus; femoral sagittal alignment, 0-3°; tibial coronal alignment, 90°; tibial sagittal alignment, 0-7°; femoral external rotational alignment, 2-5°; tibial external rotational alignment, 2-5°; and overall anatomical knee alignment at an angle of 3-7.5°valgus, the survival rate of the prosthesis could improve. Whether coronal femoral shaft bowing or sagittal femoral shaft bowing, the femoral component alignments in the coronal plane or sagittal plane were affected [7,23]. The view was further con rmed in our study.…”
Section: Discussionsupporting
confidence: 76%
“…The overall incidence of mechanical tibiofemoral angle outliers was lower in the navigation group (15.4% versus 24.9%) [23]. However, there was controversial, Chen et al [7] found that navigated TKAs resulted in a higher risk of hyperextension of the femoral components and Jae Han Ko et al [7] found that the femoral implant position was more extended in navigated TKAs than in conventional TKAs. Xu et al [24] invented an extramedullary device which was easy and convenient and this instrument could help the surgeons perform TKAs with achieving better alignment in both coronal and sagittal planes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have detailed that the use of navigation during TKA can increase the risk of anterior femoral notching because of an increased risk of placing the component in extension. 12,24,29,[36][37][38] The risk of sagittal malalignment during navigated TKA increases in patients with shorter femurs and those with increased anterior bowing, which is commonly seen in women and patients who are Asian. 15,18,[36][37][38][39] The current study showed a significant correlation between the degree of DFF and the radius of curvature of the femur.…”
Section: Discussionmentioning
confidence: 99%